Design methods with application of ergonomic requirements - Begimbai K.M., Бегимбай К.; Murzagaliyeva A., Мурзагалиева А.Б. (Рroblems of engineering and professional education, 2023)
In this paper, various methods for designing a living environment are considered, such as architectural and planning solutions, compliance with ergonomic requirements, innovative design methods, taking into account national characteristics of the organization of living space, analog architecture and computer modeling methods.